Use of a Head-Mounted Assisted Reality, High-Resolution Telemedicine Camera and Satellite Communication Terminal in an Out-of-Hospital Cardiac Arrest - Christopher S. Russi, DO; Sarayna S. McGuire, MD; Aaron B. Klassen, MD; Kate M. Skeens, MD; Kate J. Arms, NREMT-P; Lindsey D. Kaczmerick, NREMT-P; Patrick J. Fullerton, DO, MHCM; Louis M. Radnothy, DO; Anuradha Luke, MD (Mayo Clinic Proceedings: Digital Health)
Mayo Clinic Ambulance Service is testing a novel combination of technologies to enhance the ability to provide prehospital telemedicine connecting physicians with paramedics. Mayo Clinic Ambulance Service partnered with start-up company OPTAC-X to field test a novel head-mounted video camera connected with a satellite communications terminal to bring medical control emergency medicine physicians to the patient and paramedic by video. The authors believe this is the first report of a physician providing medical guidance to paramedics resuscitating an out-of-hospital cardiac arrest using these technologies.